Refugees’ experiences with online higher education: Impact and implications through the pandemic (Journal of Applied Learning and Teaching, 2023)
This paper examines and discusses refugees’ experiences with online higher education during COVID-19, a phenomenon which impacted millions of lives in displaced conditions. Through this, it unveils conditions, or lack thereof, of inclusivity as well as other unexpected concerns which have impacted refugees’ experiences through a change to online higher education which was inevitable. A scoping review of the literature is conducted to identify relevant studies that explore refugees’ experiences and challenges with online higher education during COVID-19. This has enabled an analysis which generates fresh insights into a lack of inclusion in online higher education opportunities for refugees and deeper levels of unrest impacting their experiences. As such, results are classified into three overarching themes: (1) Refugees, COVID-19, and online higher education; (2) multiplicity of barriers; (3) socio-economic status and mental health. The findings indicate that inadequate opportunities and access to online higher education persisted for refugees’ during the pandemic, impacting not only the continuity of education but also social integration, financial stability, and mental wellbeing. Stemming from the findings and reflections on the research questions, this paper presents the importance of implications for policies and practice within this arena.